The Relationship Between Principal’s Leadership and Teacher’s Discipline With Teacher’s Work Achievement - Ristuti, Ristuti; Arafat, Yasir; Mulyadi, Mulyadi (Yayasan Sembilan Pemuda Indonesia, 2022)
This study aims to determine and describe the relationship between principal’s leadership and teacher’s discipline partially and collectively with the work performance of teachers at SMP Negeri 11 Prabumulih. This study uses a quantitative method with a correlational approach (cause and effect). Data were analyzed using multiple linear regression with partial correlation and multiple correlation. The conclusions of this study are (1) There is a relationship between the principal’s leadership and the work performance of the SMP Negeri 11 Prabumulih teachers. (2) There is a relationship between teacher’s discipline and the work performance of SMP Negeri 11 Prabumulih teachers. (3) There is a relationship between the leadership of the principal and teacher’s discipline together with the work performance of the SMP Negeri 11 Prabumulih teachers. Principal’s leadership and work discipline were able to contribute to teacher’s work performance by 57.6%.